Ketika Allah "Diam": Analisis Retorika Ayub 39:4-15 - Arif Wicaksono (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat)
Arif Wicaksono, When God Is "Silent": Analysis of Rhetoric Job 39: 4-15. While referring to the contemplation of life's struggles, the book of Job is often one of the best stories in strengthening the faith of the congregation. Unfortunately, some approaches to the strengthening of faith in the book of Job take only in the first and second chapters, then immediately look at the last chapter of this book. It is rare to find the discussions touching the dialogs contained in the middle of this book. But if we want to look closely, the dialogues between Job and his friends, Job with God and God's answer to Job give a lot of life values about how believers should behave in temptation. This paper has a purpose to present one the topic of contemplation drawn from the dialogue between God and Job when God posed rhetorical questions to Job. The approach used in studying texts is a literal context approach with the aim of exploring the meaning of every word in Hebrew and the context that influences the text. What is to be expected in this discussion is that the reader can understand God's providence for the temptations his people experience in the rhetorical question raised to Job.